Answer:
(- 4, 29 ) and (
, -
)
Explanation:
7x + y = 1 ( subtract 7x from both sides )
y = 1 - 7x → (1)
2x² - y = 3 → (2)
substitute y = 1 - 7x into (2)
2x² - (1 - 7x) = 3
2x² - 1 + 7x = 3
2x² + 7x - 1 = 3 ( subtract 3 from both sides )
2x² + 7x - 4 = 0 ← in standard form
(x + 4)(2x - 1) = 0 ← in factored form
equate each factor to zero and solve for x
x + 4 = 0 ⇒ x = - 4
2x - 1 = 0 ⇒ 2x = 1 ⇒ x =
![(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/geika1bebdh49vlmy8m866aot9b5u0n47d.png)
substitute these values into (1) for corresponding values of y
x = - 4 : y = 1 - 7(- 4) = 1 + 28 = 29 ⇒ (- 4, 29 )
x =
: y = 1 - 7(
) = 1 -
= -
⇒ (
, -
)